Exploring The Relationship Between Personality Types and Learning Styles among Special Education Students in TVET: A Case Study - Hashim, Suhaizal; Azman, Anis Adibah; Che Lah, Noor Hidayah; Daud, Muhammad Faeiz (Journal of Technical Education and Training, 2025)
This study investigated how student personality types (introvert, extrovert, and ambivert) and learning styles, based on the five stimuli in the Dunn & Dunn Model, impacted special education students' interest in Technical and Vocational Education and Training (TVET) skills related to refrigeration and air conditioning. A quantitative research method was employed, focusing on students enrolled in refrigeration and air conditioning programmes at Vocational Special Education Secondary Schools in Malaysia. A total of 37 special education students participated in this study, which utilized a questionnaire as a research tool. The study examined how introverted, extroverted, and ambivert personalities influenced students' interest in the field. Additionally, it explored how various components of learning styles, including environment, emotions, sociology, physical aspects, and psychology, affected student interest. The findings indicated that most respondents had a moderately high level of individual personality classifications (introvert, extrovert, and ambivert) and a high-level learning style. The results revealed no significant link between different personality types and students' interest in TVET skills related to refrigeration and air conditioning, with a correlation coefficient of 0.296. Various personality types did not notably affect special education students' interest in the profession. This study enhanced comprehension of the interests of special education students, which could contribute to developing a more suitable and comprehensive learning approach to support student achievement in TVET skills